2010
DOI: 10.1007/s10856-010-4177-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different cross-linking conditions on the properties of genipin-cross-linked chitosan/collagen scaffolds for cartilage tissue engineering

Abstract: A cross-linking reagent is required to improve mechanical strength and degradation properties of biopolymers for tissue engineering. To find the optimal preparative method, we prepared diverse genipin-cross-linked chitosan/collagen scaffolds using different genipin concentrations and various cross-linking temperatures and cross-linking times. The compressive strength increased with the increasing of genipin concentration from 0.1 to 1.0%, but when concentration exceeded 1.0%, the compressive strength decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 42 publications
7
143
0
9
Order By: Relevance
“…31,55 A recent study showed that the properties of the genipincrosslinked chitosan/collagen scaffolds can be greatly affected by different genipin concentrations. 56 We also found that excessive crosslinking by 0.5% genipin solution resulted in poor cell attachment, demonstrated by the paucity of cells and the round cell shape on the scaffold surface 2 days after cell seeding. Further analysis of dsDNA content revealed virtually no cell viability in the 0.5% genipin-treated CDM throughout the culture period.…”
Section: Discussionmentioning
confidence: 71%
“…31,55 A recent study showed that the properties of the genipincrosslinked chitosan/collagen scaffolds can be greatly affected by different genipin concentrations. 56 We also found that excessive crosslinking by 0.5% genipin solution resulted in poor cell attachment, demonstrated by the paucity of cells and the round cell shape on the scaffold surface 2 days after cell seeding. Further analysis of dsDNA content revealed virtually no cell viability in the 0.5% genipin-treated CDM throughout the culture period.…”
Section: Discussionmentioning
confidence: 71%
“…35 The synthetic crosslinkers have potential cytotoxicity effect, but genipin derived from Gardenia jasminoides Ellis has been reported 5000 to 10,000 times less cytotoxicity than glutaraldehyde. 36,37 This study showed that compared with glutaraldehyde and EDC crosslinked scaffolds, genipin crosslinked chitosan/gelatin scaffolds could provide bigger pores for the exchange of oxygen and nutrients. And HepG2 cells could homogeneous growth in genipin crosslinked chitosan/gelatin scaffolds.…”
Section: Resultsmentioning
confidence: 95%
“…[23,42] Genipin was chosen for its ability to cross-link collagen gel with mechanical strength comparable to chemically cross-linked collagen, but with significantly lower cytotoxicity. [22,23] The three ECM-based gel formulations that were developed were primarily characterized in terms of their structure. All the gel formulations preserved a fiber mesh structure that is known to allow cellular infiltration and attachment.…”
Section: Discussionmentioning
confidence: 99%
“…A process to dissolve porcine cardiac ECM was developed, and the resulted hydrogel was crosslinked with genipin, a natural crosslinker, and chitosan, a natural linear biocompatible polysaccharide known to increase the strength and stability of collagen gels, [21] which can be cross-linked to collagen in the presence of genipin. [22,23] This allows for the preservation of the ECM biological composition and its ultrastructure, while increasing its mechanical strength, thus improving the efficacy of the injectable scaffold. We have developed three gel formulations, all based on whole pcECM that was formulated with genipin and different concentrations of chitosan (0-0.2 gr/gr), and evaluated them in terms of their mechanical properties and cell integration.…”
mentioning
confidence: 99%